Home-Heart-Walk : evaluation of an intervention to promote and monitor physical activity - Du, HuiYun (Curtin University, 2011)
Chronic heart failure is a complex and multifaceted clinical syndrome and impacts adversely on health related quality of life and also increases the risk of hospitalisation and major acute coronary events. Self-care in chronic heart failure requires lifestyle changes, such as dietary modifications, fluid restriction, medication adherence and increasing physical activity. Enhancing self-care has been shown to result in better health outcomes and improved quality of life. Promoting better self-care is an important and effective strategy in chronic heart failure management. Exercise and physical activity are part of best practice recommendation. Despite compelling evidence to support the benefits of physical activity in improving functional capacity and quality of life, physical activity adherence remains low. Many people find following physical activity recommendations more difficult than following their medication regime, fluid restriction and diet. To date, the majority of interventions have focused on improving physical functioning of people living with CHF involving supervised, clinic based exercise programs although the benefits for home based programs is evident. Nevertheless, the impressive gains people have achieved through physical activity programs are often lost as many fail to maintain a physically active lifestyle after they complete the program.Based upon a comprehensive literature review and theoretical framework, the Home-Heart-Walk has been developed. The Home-Heart-Walk is a novel theoretically informed self-monitoring intervention, sought to promote physical functioning in people living with chronic heart failure. This model is a self-administered intervention adapted from the standard six minute walk test. It comprised six months of weekly Home-Heart-Walk and monthly telephone follow-up. This doctoral project evaluated the effect of the Home-Heart-Walk in promoting physical functioning in a group people with chronic heart failure.Based upon a comprehensive literature review and theoretical framework, the Home-Heart-Walk has been developed. The Home-Heart-Walk is a novel theoretically informed self-monitoring intervention, sought to promote physical functioning in people living with chronic heart failure. This model is a self-administered intervention adapted from the standard six minute walk test. It comprised six months of weekly Home-Heart-Walk and monthly telephone follow-up. This doctoral project evaluated the effect of the Home-Heart-Walk in promoting physical functioning in a group people with chronic heart failure.Participants were followed up at three months and six months. The primary outcome was the physical function domain of the Medical Outcome Study Short Form-36. Secondary outcomes included the Six Minute Walk Test (6MWT) distance, European Heart Failure Self-care Behaviour Scale, Bandura’s exercise self-efficacy, generic health related quality of life (Medical Outcome Study Short Form-36) and disease specific (Minnesota Living with Heart Failure Questionnaire) as well as Physical Activity Scale.This thesis presents the conceptual underpinnings of a theoretically derived intervention, clinical trial methodology and the interim analysis of the first 67 participants who have completed the six-month study. All participants’ data were analysed on the basis of the intention to treat principle. Despite there were no statistical or clinical significant difference observed between the intervention and the control group at six-month follow-up, there was a significant increase in the 6MWT distance over the six-month study period, in the intervention group (p=0.05). A trend of improved self-reported health related quality of life was also observed in the intervention group, with a slight decreased Minnesota Living with Heart Failure Questionnaire score (baseline: 45.4 [95% CI: 37.0-53.9]; three-month: 41.7 [95% CI: 32.6-50.9]) compared to the clinically meaningful deterioration (increased score) in the control group (baseline: 36.3 [95% CI: 27.8-44.7]; three-month: 43.9 [95% CI: 35.3-52.6]). The deterioration observed in control group was sustained at six-month follow-up. Similarly, score in self-care behaviour was also slightly decreased (improvement) (26.2 [95% CI: 23.4-29.0] to 24.0 [95% CI: 21.6-26.3]) compared to a slight increase (deterioration) in the control group (25.6 [95% CI: 22.9-28.5] to 26.5 [95% CI: 23.4-29.6]), over the study period.While results from this interim analysis will not allow conclusion to be made on the effectiveness of the Home-Heart-Walk, they have provided preliminary data and insights into the challenge of promoting physical functioning in people living with chronic heart failure. This study highlights the challenges of achieving long-term physical activity adherence for people living with CHF. This has been demonstrated in recruitment challenges, and the refractory dimension of increasing physical activity.